Penguatan Keterampilan dan Etika Mengajar Daring melalui Microteaching bagi Mahasiswa Prodi Tadris Bahasa Inggris IAIN Palangka Raya - Zaitun Qamariah; Sabarun Sabarun; Hesty Widiastuty; Akhmad Ali Mirza (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2025)
This community service aims to strengthen online teaching skills and professional ethics among students of the English Education Department at IAIN Palangka Raya, particularly within the Microteaching practice (Praktik Mengajar I). Many students still lack a clear understanding of ethical standards in online learning and have limited experience teaching via digital platforms. In the context of 21st-century education, online teaching competencies are essential complements to conventional pedagogical skills. The practice employed mentoring and simulation methods. Mentoring was conducted through direct supervision during online teaching practices, while simulations were used to train students in responding to realistic virtual teaching scenarios. The activity was carried out in two stages: delivery of case-based materials on teaching ethics through interactive discussions, and 15-minute online teaching practices by each student, followed by feedback and reflection sessions. The results indicated active student participation in discussions and a developing ability to design and deliver online instruction in a communicative manner. This program contributes to equipping future English teachers with pedagogical readiness relevant to the challenges of distance education in the digital era